The prognostic and predictive value of IKZF1 and IKZF3 expression in T-cells in patients with multiple myeloma. (3rd October 2018) - Awwad, Mohamed H. S.; Kriegsmann, Katharina; Plaumann, Julian; Benn, Michael; Hillengass, Jens; Raab, Marc S.; Bertsch, Uta; Munder, Markus; Weisel, Katja; Salwender, Hans Jürgen; Hänel, Mathias; Fenk, Roland; et al.
ABSTRACT: Purpose : While recent studies described the role of IKZF1/3 proteins in multiple myeloma (MM) cells, few have highlighted the significance of IKZF1/3 expression in T-cells. In this study we examine the prognostic and predictive value of IKZF1/3 expression in T-cells in patients with MM stage III. Experimental design : We analysed the IKZF1/3 expression levels in T-cells from 45 MM stage I (MMI) and 50 newly diagnosed MM stage III (MMIII) patients, according to Durie-Salmon staging system, by flow cytometry to examine their prognostic and predictive value. We also combined in vivo observations with in vitro assays to determine the effect of IKZF1/3 expression on the T-cell immunophenotype and anti-tumour T-cell response in 162 MMIII patients. Results : We found that high IKZF3, but not IKZF1, expression in T-cells correlates with superior overall survival in MMIII patients treated with immunomodulatory drugs (thalidomide, lenalidomide and pomalidomide). Moreover, we show that higher IKZF3 expression in T-cells inhibits myeloma-specific T-cell response in vitro and that the immunophenotype of patients with high IKZF3 expression shows features that are contrary to the changes induced by immunomodulatory drugs. Although we observed higher IKZF3 expression levels in T-cells from patients with MMIII compared to MMI, IKZF3 expression was unaffected by the tumour microenvironment. Conclusion : In conclusion, IKZF3 expression in T-cells is a predictive value for clinical outcome in MMIII patients treated with immunomodulatory drugs due to its profound modulation of T-cell functionality.